107 Video interviewing children and young people for research purposes. (23rd February 2023) - Bichard, Elizabeth; McKeever, Stephen; Bench, Suzanne; Wray, Jo
Abstract : Background: Inclusivity of children in research is vital, especially if findings are likely to impact services designed to promote their health and wellbeing. There are ethical concerns about using technology as a tool for data collection with children, which may explain a limited evidence base. The aim of this abstract is to highlight experiences using this technology to encourage further research in this area. Method: ALPS (the heArt sibLings imPact Study) explored experiences of children who had a brother/sister with congenital heart disease. ALPS took place during the COVID-19 pandemic, necessitating use of a virtual platform. Interviews were undertaken with 17 children aged 8-17 years on Zoom. Data were collected from children across the UK through charities between September 2020 and February 2021. Parents were gatekeepers to most contact with children prior to interview. A Quick Response (QR) code was added to adverts linking to a short YouTube video designed for children to easily access study information. Prior to gaining assent children were asked about their understanding of ALPS. Paper forms were sent prior to interview, signatures were witnessed online, and forms returned in self-addressed envelopes. Results: Video interviews with children in their home environment helped to build rapport, as the researcher-initiated conversation about participants' surroundings including toys, books and photographs. Providing comfort during times of distress was more challenging but additional ethical provisions were planned to reduce any distress. This included parent presence after interview and contact after interview to check if support services were required for the child or family. Conclusion: Using video interview platforms can be a useful way to limit participant and family burden and may be cost effective approach for research teams. Evidence based, secure and safe ways to gain meaningful assent and consent online should be explored further with this population.